2009
DOI: 10.1007/s00586-009-1052-3
|View full text |Cite
|
Sign up to set email alerts
|

Non-fusion instrumentation of the lumbar spine with a hinged pedicle screw rod system: an in vitro experiment

Abstract: In advanced stages of degenerative disease of the lumbar spine instrumented spondylodesis is still the golden standard treatment. However, in recent years dynamic stabilisation devices are being implanted to treat the segmental instability due to iatrogenic decompression or segmental degeneration. The purpose of the present study was to investigate the stabilising effect of a classical pedicle screw/rod combination, with a moveable hinge joint connection between the screw and rod allowing one degree of freedom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 36 publications
1
32
0
3
Order By: Relevance
“…They reported a ROM reduction of 54% in flexion, 39% in extension, 45% in lateral bending, and 7% in axial rotation in comparison to our results of 58.2, 40.4, 46.3, and 52.5%, respectively. The differences in axial rotation could be due to screw loosening, as described by Schmidt et al [24], as the rigid fixation system they tested showed only a decrease of 26%, Abbreviations are explained in Table 1 which is in the lower range compared to other studies [21,[32][33][34][35][36]. FEA studies have shown that rod stiffness plays a major role in stabilizing the segment after treatment with a dynamic rod system.…”
Section: Discussionmentioning
confidence: 88%
“…They reported a ROM reduction of 54% in flexion, 39% in extension, 45% in lateral bending, and 7% in axial rotation in comparison to our results of 58.2, 40.4, 46.3, and 52.5%, respectively. The differences in axial rotation could be due to screw loosening, as described by Schmidt et al [24], as the rigid fixation system they tested showed only a decrease of 26%, Abbreviations are explained in Table 1 which is in the lower range compared to other studies [21,[32][33][34][35][36]. FEA studies have shown that rod stiffness plays a major role in stabilizing the segment after treatment with a dynamic rod system.…”
Section: Discussionmentioning
confidence: 88%
“…The present intact model was validated by comparing our results with those from in vitro and FE studies performed under similar boundary and loading conditions 16,18,19,34,38,48 ( Fig. 2).…”
Section: Range Of Motion and Stress Analysismentioning
confidence: 91%
“…Oktenoglu et al reported a unique biomechanical study and found that a dynamic system (dynamic rod and dynamic screws) restores the instable spinal segments to almost normal ROM (15,29). There are recent studies on PTDS with encouraging clinical results showing that PTDS provides stabilization similar to posterior rigid stabilization with fusion surgery (10, 22,23,30,39).…”
Section: Complicationsmentioning
confidence: 99%